Characterization of microsatellites for the endangered Ruta oreojasme (Rutaceae) and cross‐amplification in related species1. (22nd March 2013) - Meloni, Marilena; Reid, Andrea; Conti, Elena
Abstract : Premise of the study: Ruta oreojasme is an endangered species endemic to Gran Canaria (Canary Islands, Spain), where it occurs in small populations with disjunct distribution. Nothing is known about the genetic structure of these populations. Methods and Results: Using a microsatellite‐enriched library method, 10 microsatellite markers have been developed from R. oreojasme, all of which showed polymorphism. The transferability of the 10 markers was tested in two other Canarian endemic species, R. microcarpa and R. pinnata, as well as in the widespread species R. montana . Conclusions: Our results demonstrate the value of these newly developed microsatellite markers to investigate the genetic structure in R. oreojasme and show their potential applicability for population genetic studies in other Ruta species.